Chronic hepatitis C and fibrosis: evidences for possible estrogen benefits - Codes,Liana (2007)
The main injury caused by hepatitis C virus is the hepatic fibrosis, as a result of a chronic inflammatory process in the liver characterized by the deposit of components from the extracellular matrix. The fibrosis development leads to the modification of the hepatic architecture, of the hepatocellular function and to irregularities in the microcirculation. The tissue remodeling process observed in fibrosis has stellate cells, located at the space of Disse, as main acting agents. These cells, in response to a harmful stimulus, undergo phenotypic changes from non-proliferating cells to proliferating cells that express a- smooth-muscle actin (a-SMA), a process called as transdifferentiation. There are evidences that the oxidative stress is involved in the chronic liver disease and serves as bond between the injury and the hepatic fibrosis. A number of studies suggest that the estrogen, at physiological levels, presents an antifibrogenic action probably through an antioxidant effect, decreasing the levels of lipid peroxidation products in the liver and blood, thus inhibiting the myofibroblastic transformation of stellate cells and contributing for gender-associated differences in relation to the fibrosis development. The aim of this paper was to describe data from literature concerning the interaction between chronic hepatitis C and estrogens, pregnancy, use of oral contraceptives, menopause and hormone reposition therapy.